Incidence of concha bullosa and its role in chronic rhinosinusitis - Lakshmi, Yalagandula Vijaya; Singh, Thakur Dinesh; Fathima, Razia; Kumar, Vaddi Hemanth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Pneumatization of nasal turbinates is called concha bullosa. Most often it involves the middle turbinate and is one of the commonest variants of sinonasal anatomy. Bulbous and extensive type of concha bullosa may lead to narrowing or even complete blockage of osteomeatal complex. This alters the normal airflow and drainage pathways of mucous, resulting in mucosal edema which obstructs the ethmoidal infundibulum and osteomeatal obstruction leading to sinusitis. The aim of the study was to determine the incidence of concha bullosa and assess its role in causation of chronic rhinosinusitis. The objective was to determine the incidence of concha bullosa and assess its role in chronic rhinosinusitis. Methods: A retrospective study of 120 patients suffering from chronic sinusitis of age group 18 years to 70 years old were taken between March 2018 to January 2021 at Malla Reddy institute of medical sciences (MRIMS) who had nasal symptoms significant enough to warrant a CT paranasal sinus (CT PNS) with positive findings. All PNSs involved were identified for sinus disease. Concha bullosa identified and graded into small, moderate and large. Patients with history of previous nasal surgeries were excluded. Results: Our study showed 54% cases of chronic sinusitis with concha bullosa. Conclusions: Concha bullosa may be one of the predisposing factors of chronic rhinosinusitis and hence surgical manipulation by functional endoscopic sinus surgery (FESS) is important to prevent recurrence of sinusitis.